Prince of cats ebook - Wimberly, Ronald (Image Comics, 2016)
PRINCE OF CATS is the B side to Shakespeare's Romeo and Juliet, played at an eighties block party in an NY where underground sword dueling blossomed alongside hip-hop, punk, disco, and no wave. Itês the story of the minor players with Tybalt at the center. The definitive printing of RONALD WIMBERLY's critically-acclaimed first work, presented as intended for the first time.. Author: Ronald Wimberly. Illustrator: Ronald Wimberly . 2016 Ronald Wimberly.